Coparentalidade: evidências teoricamente fundamentadas para validar a escala da relação coparental (versão brasileira) - Carvalho, Thaís Ramos de (Universidade Federal de São Carlos, 2020)
Coparenting is a term used to refer to how parents (or other parental figures) interact, when deciding how to handle their parenting roles. The coparental relationship has important effects on children’s development and the well-being of parents. The Coparenting Relationship Scale, an instrument developed to evaluate coparenting, has already undergone a cross-cultural adaptation process for use in Brazil, where it is called the Escala da Relação Coparental (ERC). The objective of the present study was to look for evidence, based on theoretical concepts of accuracy and validity of the ERC, based on its internal structure (using confirmatory factor analysis and tests for invariance) and association with external variables (to examine discriminant validity and correlations with tests that evaluate related constructs). Data were collected with 433 parents (238 mothers and 195 fathers) who had at least one child of up to 6 years of age. In addition to the ERC, instruments were applied to evaluate the relationships among ERC scores and measures of: (a) social desirability (to examine discriminant validity), (b) child adjustment, (c) marital satisfaction, (d) depression, (e) parental stress, and (f) social skills. Based on a confirmatory factor analysis, the internal structure of the Brazilian ERC included the same six factors that had satisfactory levels of reliability, and that formed the original American structure. In addition, there was evidence for invariance of the structure of the instrument, in relation to gender, at the configural, metric and scalar levels. With respect to accuracy, all ERC subscales presented values considered to be acceptable or satisfactory. With respect to evidence of discriminant validity, statistically significant correlations were found between only two ERC factors (undermining and conflict) and the total score of the social desirability instrument, and only for fathers. With respect to marital status and depression, most of the correlations were significant, which supports the study hypotheses. For child adjustment and parental stress, a significant number of correlations was observed, but for social skills, most of the correlations were not significant and these results differed from the study hypotheses. In addition, some correlations between the ERC subscales and the social skills instrument, although significant, were in the opposite direction than was expected, for the mothers. These results provide substantial evidence for the accuracy and validity of the ERC, besides confirming theoretical concepts about variables associated with the coparenting relationship. However, two limitations of the study were the low number of participants who responded to each of the instruments (with the exception of the ERC) and the low variability of responses for some of the constructs being evaluated, making it difficult to verify the existence of the expected correlations. Finally, it is noteworthy that the development of a brazilian instrument to evaluate coparenting, that has satisfactory evidence of accuracy and validity, may be useful in the context of scientific research as well as in intervention settings.
Coparenting: theoretically based evidence to validate the coparenting relationship scale (brazilian version)
Keywords: Coparentalidade; Instrumento; Precisão; Validade; Coparenting; Instrument; Accuracy; Validity; CIENCIAS HUMANAS::PSICOLOGIA